„Schmerzlos sind wir und haben fast | Die Sprache in der Fremde verloren“ - Faber, Bettina (Annali di Ca’ Foscari: Serie Occidentale, 2024)
Recent research has rightly emphasized the extent to which Hölderlin’s poetry opens up broad horizons of transcultural perspectives with a thoroughly cosmopolitan intention. However, these great drafts of ‘transtopias’ remain in the realm of speculative idealism, as long as one ignores the counterpoint that Hölderlin sets up with his contemporaneous texts about the experience of extreme individual danger and distress. Only against this background of struggle for self-preservation in hard and “godforsaken” times, Hölderlin’s ingenious, still hopeful rather than deconstructive intuitions gain real credibility and relevance.